2010
DOI: 10.1016/j.nurt.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Statins in Traumatic Brain Injury

Abstract: Summary: Traumatic brain injury (TBI) is a common cause of long-term neurological morbidity, with devastating personal and societal consequences. At present, no pharmacological intervention clearly improves outcomes, and therefore a compelling unmet clinical need remains. 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, or "statins," offer a potential novel therapeutic strategy for TBI. Statins are well tolerated, easy to administer, and have a long clinical track record in critically ill patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 97 publications
(151 reference statements)
0
50
0
Order By: Relevance
“…17 Lastly, statins counteract the procoagulant cascade promoted by infl ammation through the following mechanisms: blunting monocytic expression of tissue factor, increasing thrombomodulin availability (important in the activation of protein C), and reducing levels of plasminogen activator inhibitor-1, which impairs the fi brinolytic system. 15 Though no studies to date have evaluated the effect of statins on delirium in patients in the ICU, this drug class has been examined in models of traumatic brain injury (TBI), 18 which involves pathophysiologic changes (eg, neuronal damage and apoptosis, neuroinfl ammation, and BBB injury) similar to those observed in other types of critical illness, including sepsis and acute respiratory distress syndrome. The benefi ts of statins observed in animal studies of TBI include increased hippocampal neuron survival and improved neurologic function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Lastly, statins counteract the procoagulant cascade promoted by infl ammation through the following mechanisms: blunting monocytic expression of tissue factor, increasing thrombomodulin availability (important in the activation of protein C), and reducing levels of plasminogen activator inhibitor-1, which impairs the fi brinolytic system. 15 Though no studies to date have evaluated the effect of statins on delirium in patients in the ICU, this drug class has been examined in models of traumatic brain injury (TBI), 18 which involves pathophysiologic changes (eg, neuronal damage and apoptosis, neuroinfl ammation, and BBB injury) similar to those observed in other types of critical illness, including sepsis and acute respiratory distress syndrome. The benefi ts of statins observed in animal studies of TBI include increased hippocampal neuron survival and improved neurologic function.…”
mentioning
confidence: 99%
“…The benefi ts of statins observed in animal studies of TBI include increased hippocampal neuron survival and improved neurologic function. [18][19][20][21][22] In humans, one clinical trial reported a reduction in amnesia and increased orientation in patients with TBI who were treated with rosuvastatin. 23 Studies investigating the effect of statins on patients with postoperative delirium, a population with different clinical profi les than patients in the ICU, have yielded inconsistent results.…”
mentioning
confidence: 99%
“…Total 44 100 P E R S P E C T I V E (27), and brain injury (28,29). A search of the literature reveals no systematic neuroPK studies in any mouse strain that would enable direct comparisons of CNS exposure across the various statins.…”
Section: Databases and Repurposingmentioning
confidence: 99%
“…Statin therapy has also been investigated in patients with ALI; it was shown to be safe and associated with a significant decrease in bronchoalveolar lavage interleukin-8, but had no other effects compared to placebo [101]. Although preclinical studies have shown benefits from statins in models of TBI and related disease processes, including cerebral ischemia, ICH, and subarachnoid hemorrhage, clinical studies have been shortcoming [102]. The use of statins in patients with aneurysmal subarachnoid hemorrhage has been investigated in several small clinical trials.…”
Section: Statinsmentioning
confidence: 99%